Needs for processing career promotion course to add value for freshwater fish farmers in Nakhon Sawan Province - Khrueahong, J.; Poungsuk, P.; Junlex, P. (My University, 2025)
Results revealed that the respondents needed training courses for fish crackers, dried fish strips, sour pickled fish, fish sausage, and fermented fish. They needed a 1-2 days training course at the training place in the village during the off-season for rice growing. The participants should be around 21-30 persons and the training program that informed at least one week in advance. Training activities should focus on actual practice (91.50%) and the training organizer must be responsible for expenses (99.02%). Each time of the training should have only one topic (x̅= 3.55; S.D = 1.08). Assessment through observation during the training should be done (x̅= = 3.77; S.D. = 0.58) and assessment after the training must be conducted (x̅ =3.75, S.D. = 0.79), For the training session, it should include demonstration (x̅ = 4.23, S.D. = 0.67) actual practice (x̅ = 4. 40, S.D. = 0 . 61) and diverse use of media (x̅ = 4. 29, S.D. = 0.68). According to the comparison, there was a statistical difference between the needs for training and the socio-economic attributes of the respondents. The latter included sex, educational attainment, farmer group membership, number of household labor, and debts or sources of loans. A training course for value-added processing of freshwater fish has tended to develop for future training sessions with farmers.
Keywords: Farmers; Freshwater fish; Processing career; Training course